Cape Rage - Book 2 - Corbett, Ron, 1959- (Thorndike, Maine : Center Point Large Print, 2024)
"The FBI has a hundred undercover agents who can work in the city, but Danny Barrett is the one they call when they need someone to investigate crimes in the wilderness. This case is a particularly difficult one. For more than a century the Danby family have ruled as kings in their corner of the Pacific Northwest. The Feds were mostly willing to look the other way while the family smuggled everything from liquor to cigarettes across the border, but lately things have taken a darker turn. A recent bank robbery in Seattle looks like it may have been committed by the Danbys, but theres no way the FBI can get any locals to turn against them. Only Danny Barrett has what it takes to get inside the organization and shut them down. But before Danny can do that hes going to have to contend with Henry Carter, a former Danby in-law and current psychopath. The Danbys thought they left Henry for dead in the deepest part of the woods, but hes coming back. Hell go to hell to get his revenge, and hes willing to take the whole family with him."--
Keywords: Barrett, Danny -- (Fictitious character) -- Fiction; United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Undercover operations -- Fiction; Wilderness areas -- Fiction; Revenge -- Fiction; Organized crime -- Fiction; Washington (State) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Large print books